'True' as Polysemous. (2nd October 2021) - Yu, Andy
Abstract: In this paper, I propose that 'true' is polysemous and thus ambiguous. I suggest that the semantic paradoxes both motivate taking 'true' to be polysemous and show that the concept truth is indefinitely extensible. In doing so, I explain that 'true' is polysemous between the meanings corresponding to the subconcepts of the concept truth generated by such indefinite extensibility. I conclude that the proposal provides satisfying solutions to the semantic paradoxes.